OVERVIEW OF GNSS SYSTEMS AND THEIR OPERATION - Boštjan Krošelj; Dalibor Igrec (Journal of Energy Technology, 2023)
In this paper, we present the beginnings of navigation and what it was that drove its development forward. We will also present the development of global navigation satellite systems, known as GNSS, as well as all the most important GNSS systems and their development. Finally, the basic operation of such systems and the differences between them will be presented.